2007
DOI: 10.1172/jci28031
|View full text |Cite
|
Sign up to set email alerts
|

IL-17–dependent cellular immunity to collagen type V predisposes to obliterative bronchiolitis in human lung transplants

Abstract: Bronchiolitis obliterans syndrome (BOS), a process of fibro-obliterative occlusion of the small airways in the transplanted lung, is the most common cause of lung transplant failure. We tested the role of cell-mediated immunity to collagen type V [col(V)] in this process. PBMC responses to col(II) and col(V) were monitored prospectively over a 7-year period. PBMCs from lung transplant recipients, but not from healthy controls or col(IV)-reactive Goodpasture's syndrome patients after renal transplant, were freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
404
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 370 publications
(431 citation statements)
references
References 43 publications
24
404
1
2
Order By: Relevance
“…34 Moreover, pretransplant patients who show collagen (V) reactivity have an increased incidence of early graft dysfunction following transplantation. 35 Most recently, two groups have shown that a highly purified population of Th17 cells is capable of inducing lethal GVHD, hallmarked by extensive pathologic cutaneous and pulmonary lesions.…”
Section: Discussionmentioning
confidence: 99%
“…34 Moreover, pretransplant patients who show collagen (V) reactivity have an increased incidence of early graft dysfunction following transplantation. 35 Most recently, two groups have shown that a highly purified population of Th17 cells is capable of inducing lethal GVHD, hallmarked by extensive pathologic cutaneous and pulmonary lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune processes have also been shown to play a role. Exposure of typically cryptic antigens such as type-V collagen and K-a1 tubulin during the lung transplant process may help drive the CLAD process (Burlingham et al 2007;Goers et al 2008).…”
Section: Chronic Lung Allograft Dysfunctionmentioning
confidence: 99%
“…Thus, mutations in the genes encoding either ␣1(V) or ␣2(V) chains result in the human connective tissue disorder classic Ehlers-Danlos syndrome, characterized by collagen I fibrils of abnormal shapes and diameters and deficient tensile strength (7,8). More recently, it has been demonstrated that anti-col(V) autoimmune responses can underlie chronic lung transplant rejection in both humans (9) and animal models (10) and that pre-transplant col(V)-specific autoimmunity is also a significant risk factor for primary graft dysfunction, the leading cause of early morbidity and mortality after lung transplantation (11,12). Col(V) autoimmunity has also been identified as a consistent feature in both late stage human coronary artery disease and a mouse model of atherosclerosis (13).…”
Section: Collagen Type V (Col(v))mentioning
confidence: 99%